'Peripheric' pancreatic cysts: performance of CT scan, MRI and endoscopy according to final pathological examination. Issue 6 (June 2015) - Duconseil, P.; Turrini, O.; Ewald, J.; Soussan, J.; Sarran, A.; Gasmi, M.; Moutardier, V.; Delpero, J.R.
Abstract: Objective: To assess the accuracy of pre‐operative staging in patients with peripheral pancreatic cystic neoplasms (pPCNs). Methods: From 2005 to 2011, 148 patients underwent a pancreatectomy for pPCNs. The pre‐operative examination methods of computed tomography (CT), magnetic resonance imaging (MRI), endoscopic ultrasonography (EUS) were compared for their ability to predict the suggested diagnosis accurately, and the definitive diagnosis was affirmed by pathological examination. Results: A mural nodule was detected in 34 patients (23%): only 1 patient (3%) had an invasive pPCN at the final histological examination. A biopsy was performed in 79 patients (53%) during EUS: in 55 patients (70%), the biopsy could not conclude a diagnosis; the biopsy provided the correct and wrong diagnosis in 19 patients (24%) and 5 patients (6%), respectively. A correct diagnosis was affirmed by CT, EUS and pancreatic MRI in 60 (41%), 103 (74%) and 80 (86%) patients (when comparing EUS and MRI; P = 0.03), respectively. The positive predictive values (PPVs) of CT, EUS and MRI were 70%, 75% and 87%, respectively. Conclusions: Pancreatic MRI appears to be the most appropriate examination to diagnose pPCNs accurately. EUS alone had a poor PPV. Mural nodules in a PCN should not be considered an indisputable sign of pPCN invasiveness.